In Search of the City - Helen J. Maib (Oz, 1989)
Where does one find the city? Is it in a cluster of buildings, a pattern of streets, a collection of cultural amenities and civic services, or a residential neighborhood? Does it always include congestion, blight, pollution, and other manifestations of urban decay?